Relationship of Stock Returns with Firm Size, Book-to -Market Equity Ratio and Earning-to-Price Ratio in Tehran Stock Exchange - Majid Shariat Panahi; Farman Khosravi (مطالعات تجربی حسابداری مالی, 2007)
The capital asset pricing model (CAPM) states the equilibrium relationships between risk and expected return. This model argues that only systematic risk should be priced in the market; specific or idiosyncratic risk does not get a risk premium. Despite the CAPM being a more useful model in the financial and investment profession.  However, recent empirical studies have raised serious challenges to this belief. It appears that "B" as a measure of systematic risk, has little power in explaining cross-sectional risk and return relationship over - term periods, but it has been observed that other variables such as "firm size" and "book - to - market ratio" and "earning - to - price ratio", (Fama &  French three factors) appear to be more useful risk proxies. This study seeks to explore the cross-sectional determinants of common stock returns (except investment Company) in Iranian emerging stock market, namely Tehran stock Exchange for the period 2000 through 2004.  The joint roles of stock returns measured by firm size (ME), book-to-market equity ratio (BE/ME) and earning-to-price ratio (PIE) on monthly returns are examined. The study findings although consistent with central theme of the CAPM, but are inconsistent with the results of similar studies carried out in major developed stock markets recently.